2021
DOI: 10.1016/j.plabm.2021.e00236
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-based S100B testing for management of traumatic brain injury in emergency setting

Abstract: Background Serum biomarker S100B has been explored for its potential benefit to improve clinical decision-making in the management of patients suffering from traumatic brain injury (TBI), especially as a pre-head computed-tomography screening test for patients with mild TBI. Although being already included into some guidelines, its implementation into standard care is still lacking. This might be explained by a turnaround time (TAT) too long for serum S100B to be used in clinical decision-making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…The mean level of S100B in patients with SED in the current study (0.388 ng/ml) exceeded a suggested reference level used to identify pathological CT scans in hospital emergency settings after traumatic brain injury (≥ 0.105 ng/ml) 15 . However, caution must be used in interpreting the meaning of this difference, as the previous study used a different method to measure serum levels of S100B (the Elecys ® S100 assay on a Cobas e411 instrument, both from Roche Diagnostics, Germany).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The mean level of S100B in patients with SED in the current study (0.388 ng/ml) exceeded a suggested reference level used to identify pathological CT scans in hospital emergency settings after traumatic brain injury (≥ 0.105 ng/ml) 15 . However, caution must be used in interpreting the meaning of this difference, as the previous study used a different method to measure serum levels of S100B (the Elecys ® S100 assay on a Cobas e411 instrument, both from Roche Diagnostics, Germany).…”
Section: Discussioncontrasting
confidence: 62%
“…S100B is a cytosolic calcium-binding protein 13 synthesized primarily by astrocytes 14 . Raised levels of S100B are used clinically as an indicator of brain damage 15 and may be a marker of neurological disorders 16 . S100B is hypothesized to be a marker of blood brain barrier integrity 17 and has been found in the cerebrospinal fluid (CSF) and serum of patients with mood disorders, including MDD 18 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Establishing a TBI biomarker, potentially the S100B protein, could possibly decrease the number of unnecessary CT scans performed for patients after head trauma and economize hospital costs [31]. Our study does not include a cost-effectiveness analysis, but each biochemical test performed serially is cheaper than an imaging test.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that plasma-based S100B detection is superior to serum-based detection, significantly reducing processing time (Ref. 71 ). GFAP is a specific intermediate filament protein found in astrocytes and is upregulated during astrocyte proliferation.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%